Long-baseline fluid tiltmeter for seismotectonic studies of Mexican subduction zone - Marina Manea (Geofísica Internacional, 2002)
A long-baseline water tiltmeter (LBT) was constructed on the Pacific coast of Mexico to provide high precision tilt observationsin a section of the subduction zone apparently undergoing interseismic-preseismic deformation phase. Continuous tilt complementsGPS and vertical displacement (leveling) measurements by providing higher precision and continuous data. The plateinterface is reasonably well located from local seismicity and gravity anomalies. Integrated geodetic and seismicity observationsenabled us to monitor the strain near the upper and lower ends of a seismogenic zone on which a future M~7.0 earthquake isnucleating. Predicting the future rupture may be possible because the instrument is two orders of magnitude more sensitive thanother monitoring devices in the region. Main principles, technical features and installation procedure of the water LBT and somepreliminary observations and results are presented.